STUDY ON THE LAW PROTECTION ASPECT OF COOPERATING WITNESS ACTORS (JUSTICE COLLABORATOR) IN THE NARCOTIC CRIME CONNECTED WITH THE LAW PRINCIPLES - Kholiq, Abdul; Garwan, Irma (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the regulation of witnesses who collaborate (justice collaborator) in relation to efforts to provide legal protection by considering the principle of legal certainty. The research method used is a normative juridical research method, the approach used is the statutory approach, conceptual approach and case approach. The analysis technique in this study uses qualitative analysis. The results of this study indicate that several regulations that contain legal protection for witnesses who collaborate (justice collaborator) in Law Number 13 of 2006 are subsequently changed to Law Number 31 of 2014 on Witness and Victim Protection, as well as in the Supreme Court Circular Number 4 of 2011. Whereas the protection efforts must be based on a sense of community justice and legal certainty guarantees by law enforcement officials.